Teacher Candidate Perceptions of Urban Field Experiences - Smith, Linda; Farnan, Shantel; Seeger, Victoria; Wall, Timothy Jason; Kiene, David (Educational (Re)naissance, 2018)
This paper examines the impact of diverse clinical field experiences on rural teacher candidates’ perceptions of their ability to effectively teach urban, diverse students. The literature framework supporting the study builds on Nieto’s description of socially-just pedagogy and responsive approach to diversity while meeting national education program standards despite declining resources. Researchers gauged candidates’ perceptions of the impact of working with students from race, language and class backgrounds different from their own. Findings revealed four significant impacts: increasing capacity to use culturally-relevant practice, boosting ability to differentiate for urban learners’ diverse needs, understanding the importance of strong relationships, and raising candidate self-efficacy and desire to teach in diverse schools.